Centrifuge study of reinforced soil walls with different backfill compaction densities. Issue 5 (5th October 2020) - Xu, P.; Hatami, K.; Jiang, G.
Abstract : Backfill relative density can have a significant influence on the performance and stability of reinforced soil retaining walls, as reflected in the form of minimum compaction requirements in current design guidelines. However, the quantitative influence of backfill relative density on the construction and serviceability performance of reinforced soil walls has not been examined adequately. In this study, centrifuge tests were carried out on two model walls with different backfill relative densities, and their measured performances were compared against those calculated using available empirical methods. Results of the study show that maximum displacement of the model with inadequate compaction (i.e. D r = 65%) was 30% greater than that of the D r = 95% model and exceeded the value predicted by one of the design methods examined. The foundation pressure underneath the wall showed increased magnitudes under the facing and a nonlinear decrease with distance from the facing along the backfill. Additionally, the model with D r = 95% developed larger reinforcement loads and mobilized soil-reinforcement interface coefficient values relative to the model with D r = 65%.